Synthesis of silver nanoparticles in hydrogels - Schelestow, Kristina (Pontificia Universidad Católica del Perú, 2018)
The present work is concerned with the fabrication of a novel hydrogel-silver hybrid material, the characterization regarding its structural and antibacterial properties and the investigation of its interaction with glass surfaces. Hydrogels based on N-isopropylacrylamide, a functionalized macromonomer of 2-oxazolines and N,N'-methylene bisacrylamide as a cross-linker were synthesized via radical polymerization using ammonium persulfate and N,N,N,N'-tetramethylene diamine as initiator system. By complexion with silver cations from a silver nitrate solution and a subsequent reduction with sodium borohydre, silver nanoparticles inside the polymer network were formed. Bulk hydrogels of different composites were characterized concerning their structure and their water absortive capacity. The formation of silver nanoparticles as well as its influencing factors were analysed and could be confirmed quantitavely. The antibacterial activity of the developed composite material in this powder form was determinated via count test applying it to Staphylococcus aureus. The number of bacteria could be reduced to approximately 0.1% compared to the reference value without silver nanoparticles. Thus, the hydrogel-sliver hybrid can be appraised as suitable for biomedical applications. Finally, different hydrogel layers were produced on fotosensitive glass FS21 and evaluated regarding their applicability for microsystems technology.
Keywords: Productos nuevos--Materiales; Coloides; Nanopartículas; Materiales; https://purl.org/pe-repo/ocde/ford#2.05.01